Voltammetric determination of sulfite using graphite paste electrode modified with nanoparticles of copper pentacyanonitrosylferrate - Do Carmo, Devaney Ribeiro [UNESP]; Silvestrini, D. R. [UNESP]; Cumba, L. R. [UNESP]; Souza, M. M. [UNESP] (The Electrochemical Society, 2012)
Copper Pentacyanonitrosylferrate (NCuNP) nanoparticles were prepared in formamide solvent. The material was characterized by Infrared (FTIR), X-Ray Diffraction (XRD) and Ultraviolet-Visible (UV-Vis) Spectroscopy. The Cyclic Voltammogram (CV) the modified graphite paste electrode with NCuNP exhibits two redox couples with (Eθ,)1 = 0.29 and (E θ,)2 = 0.86 V attribute at Cu(I)/Cu (II) and Fe(II)(CN)5NO/Fe(III)(CN) 5NO processes, respectively (KCl = 1.0 mol L-1; v = 20 mV s-1). The redox couple with (Eθ,)2 presents an electrocatalytic response for sulfite. The modified graphite paste electrode gives a linear response of 7.0 × 10-4 to 3.0 × 10-2 mol L-1 (r = 0.998), for sulfite determination with Detection Limit (DL) of 1.76 × 10-3 mol L-1 and an amperometric sensitivity of 3.38 mA/mol L-1 and relative standard desviations ± 3% (n=3). ©The Electrochemical Society.
Keywords: Amperometric; Cyclic voltammograms; Detection limits; Electrocatalytic response; Graphite paste electrode; Linear response; Modified graphites; Voltammetric determination; Copper; Fourier transform infrared spectroscopy; Nanoparticles; X ray diffraction; Graphite